(untitled) (Journal of the College of Basic Education, 2023)
If reading is one of the windows of knowledge, and one of the most important tools of education by which a person stands on the results of human thought, then writing is - in fact - the pride of the human mind, rather it is the greatest thing that the mind has produced. (Fadlallah, 2008: 53), (Madkour, 2009: 265), and (Al-Khaffaf, 2014: 196).Writing is the greatest discovery made by man during his long history, with which he was able to record his production and heritage, and to take from the past and present what prepares the way for subsequent generations. (Al-Jaafrah, 2011: 273).